2007
DOI: 10.1007/s00296-007-0404-8
|View full text |Cite
|
Sign up to set email alerts
|

Tender point count and total myalgic score in fibromyalgia: changes over a 28-day period

Abstract: Tender point count (TPC) is central to fibromyalgia syndrome (FMS), and with total myalgic score (TMS) is often used to monitor the patient's condition. This study aimed to determine the stability of TPC and TMS over time, and to examine how well these measures reflected patients' perceptions of their condition. Twenty-four patients with FMS completed the Fibromyalgia Impact Questionnaire (FIQ) and a visual analogue scale (VAS) measuring well-being, at entrance into the study, and 7 and 28 days later. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…Our findings concur with previous studies showing lower pain thresholds in some specific points such as occiput, anterior cervical, or second rib. Particularly, the anterior cervical was the tender point with higher sensitivity in the fibromyalgia group, which is consistent with previous studies [24][25][26]. However, this tender point was also observed to be the most sensitive to pressure in controls.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings concur with previous studies showing lower pain thresholds in some specific points such as occiput, anterior cervical, or second rib. Particularly, the anterior cervical was the tender point with higher sensitivity in the fibromyalgia group, which is consistent with previous studies [24][25][26]. However, this tender point was also observed to be the most sensitive to pressure in controls.…”
Section: Discussionsupporting
confidence: 91%
“…Tender points were the variables with the largest effect sizes of all variables studied, which reinforces pain as the most predominant and distinctive symptom in fibromyalgia [23]. Previous literature supports that fat tissue thickness, soft tissue surfaces, and/or closeness to bone muscle and nerve tissues might influence pain-pressure levels [24][25][26]. Our findings concur with previous studies showing lower pain thresholds in some specific points such as occiput, anterior cervical, or second rib.…”
Section: Discussionsupporting
confidence: 89%
“…They concluded that digital tender point count seemed to be suYcient for the assessment, and there is no need for an additional instrument for tender point evaluation. In the study by Mc Veigh et al [8] performed with 24 patients, the alteration between TPC and total myalgic score (TMS) and correlation with FIQ was investigated in a period of 28 days. They did not Wnd any correlation with FIQ and did not observe signiWcant alteration in TPC.…”
Section: Discussionmentioning
confidence: 99%
“…Second, tenderness assessed by the tender point count does not reflect particular clinical entity and may be an indication of allodynic or hyperalgesic responses associated to peripheral or central sensitization mechanisms [38]. Third, tender point count is variable with time within the same subject [39] and it is clearly influenced by psychological variables, such as individual's distress [40]. Fourth, tender point count is not associated with disability or pain intensity [39,41].…”
Section: Myofascial Pain Versus Fibromyalgia: Trigger Versus Tender Pmentioning
confidence: 99%
“…Third, tender point count is variable with time within the same subject [39] and it is clearly influenced by psychological variables, such as individual's distress [40]. Fourth, tender point count is not associated with disability or pain intensity [39,41]. Furthermore, tender points are not sites of ongoing inflammation since no differences in concentrations of chemical mediators, for example, ATP, PGE2, glutamate, glucose, pyruvate and urea are observed between tender and nontender points [42].…”
Section: Myofascial Pain Versus Fibromyalgia: Trigger Versus Tender Pmentioning
confidence: 99%